Graphene-Based Steganographic Aptasensor for Information Computing and Monitoring Toxins of Biofilm in Food - Wang, Qi; Yang, Qingli; Wu, Wei (Frontiers in Microbiology, 2020)
Fungi forming biofilm would produce various toxin in food. The toxin contamination will cause great harm to food and human health. Herein, a novel graphene-based steganographic aptasensor was assembled for multifunctional applications, which depended on the specific recognition and information encoding ability of DNA aptamers (mycotoxins, including zearalenone (ZEN) and ochratoxin A (OTA) aptamers, as models) and the selective absorption and fluorescence quenching capacities of graphene oxide (GO). The graphene-based steganographic aptasensor can be regarded as an information encryption and steganographic system using GO as a cover, aptamers for specific target recognition as information carriers and dual targets (ZEN and OTA) as special keys. In our work, the fluorescence of capture probes (Cy3-aptamer and Alexa Fluor 488-aptamer) was quenched by GO to realize information encryption. In the presence of dual targets in the GO-APT solution, Cy3-aptamer (APT1) and Alexa Fluor 488-aptamer (APT2) were released from the surface of GO, decrypting the hidden information. In addition, our work offers a sensor for rapid and sensitive simultaneous fluorescence determination of ZEN and OTA. The detection limit of the aptasensor was 0.72 ng/mL for ZEN and 0.25 ng/mL for OTA. In addition, the graphene-based steganographic aptasensor can be used to construct a molecular logic gate system in which GO, apatmers, and mycotoxins are employed as the input, and compounds and fluorescence signals were used as the output. This would be helpful to control the biofilm toxin in the future.